Informasi Kesehatan Pendengaran Pada Bayi dan Anak Melalui Program Kesehatan TVRI NTB - Yuliyani, Eka Arie; Putu Aditya Wiguna; Ika Primayanti; Anak Agung Ayu Niti Wedayani (Universitas Mataram, 2024)
As one of the modern media, television has an important role in conveying various information, including about the world of health. Through attractive and audio-visual displays, television can make it easier for people to receive the health information conveyed. Commemorating world hearing day, TVRI NTB station collaborates with Unram Hospital to provide health education through the